Ujaran Seksisme Yoshiro Mori: Persoalan Stereotip Gender Pada Olimpiade Tokyo - Sulatri, Ni Luh Putu Ari (Vocational College of Diponegoro University, 2021)
The head of the Tokyo Olympics, Yoshiro Mori, was criticized for making sexist remarks. He gave opinion about the Japanese Olympic Committee's goal of increasing the number of female board directors from 20% to more than 40%, Mori stated that it would affect the length of the meeting because women talking too much. Mori's sexist remarks show that patriarchy and gender equality are still a problem in Japan. This paper examines Yoshiro Mori’s sexist remarks through a feminist approach. Data culled from newspaper reports about Mori's sexist remarks. This research is qualitative research with an interactive analysis method. The results of the study show that Mori's sexist remarks are gender stereotypes that are concluded by essentialism. These gender stereotypes limit the role of women in the public sphere. Collective action needs to be promoted to confront sexism in society and build gender awareness.